Stability analysis and improvement evaluation on residual soil slope with reinforcement load : building cracked & slope failure - Goh, Jee Ren (2018)
Slope failure is a very serious geologic hazard in many states of Malaysia. In this country, most cases of the tragedies involved a hillside area such as IIUM, Kuantan campus which found that the building and road utilities which loading directly on the slope was damaged due to slope failure and landslide. This project study focused on the soil properties and parameters which affected the stability of residual soil slope against failure and producing the stability of slope with higher FOS by using design concept of soil-structure reinforcement. The project employed several approaches i.e. field monitoring and surveying, laboratory experimental and stability modelling analysis with SLOPE/W (2007). A field monitoring works carried out to collect soil samples and also photogrammetry (photo capture surveying). The samples collection were tested with at geotechnical soil laboratory for soil index test to provide soil properties and shear test to provide shear strength parameters. The stability modeling (SLOPE/W) was applied based on the laboratory experimental results to obtain the appropriate factor of safety for the typical slope. . This project study demonstrated the slope to be failure with FOS of 0.828 which lower than the minimum standard of 1.4 due to the increasing of moisture content and caused a drop in both cohesion and angle of internal friction. Therefore, reinforcement load was added to improve the stability of typical failed slope with different materials of ground anchor, soil nailing, geo-fabric and driven pile. All the reinforcement loads increased the stability of residual slope with the highest FOS of 2.911, 2.911, 1.624 and 2.982 respectively. Driven pile showed the highest tensile shear strength when bonding between soil and structure load. Besides, combination reinforcement load was an inventive and innovative design for stability improvement in this project study. The combination reinforcement also increased the slope stability with the highest FOS of 2.919 (anchor +pile), 2.615 (anchor +fabric+pile), 2.201 (anchor +fabric), and 1.915(fabric+pile). This project study was delivered a strong belief that single and combination reinforcement load both can improve soil properties and parameters in slopes designs.